Forage diversity and nutrition supply of reindeer - Staaland, Hans; Sæbø, Stein (Rangifer, 1993)
This study describes the mineral and nitrogen concentrations of reindeer forage plants from the Elgå reindeer herding district of south-eastern Norway. The data are compared with results from 5 other areas in Norway. Emphasis is put on the importance of environmental diversity. Different plant species accumulate Ca, Mg, P, S, Na, K, CI and K to a varying degree but reindeer can meet their nutritional requirements by eating different types of forage. Examples are sodium from aquatic herbs, sulphur and sodium from horsetails etc. Of further importance are variations in soil type, phenological development of plants in relation to differences in time for snowmelting, as well as different levels of nutrients in forage from different geographical.